2020
DOI: 10.1021/acs.chemmater.0c02708
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Solar Energy Storage under Ambient Conditions in a MOF-Based Solid–Solid Phase-Change Material

Abstract: This paper demonstrates a metal–organic framework (MOF) containing photoswitches within the pores as a hybrid solar thermal fuel (STF) and solid–solid phase-change material (ss-PCM). A series of azobenzene-loaded MOFs were synthesized with the general formula Zn2(BDC)2(DABCO)­(AB) x (BDC = 1,4-benzenedicarboxylate, DABCO = 1,4-diazabicyclo[2.2.2]­octane, AB = azobenzene, where x = 1.0, 0.9, 0.5, 0.3), herein named 1⊃AB1.0, 1⊃AB0.9, 1⊃AB0.5, and 1⊃AB0.3 respectively. X-ray powder diffraction, solid-state NMR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
85
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(104 citation statements)
references
References 75 publications
16
85
2
1
Order By: Relevance
“…In the 13 C cross-polarisation (CP) magic-angle spinning (MAS) NMR spectrum of 1IMOAB (Fig. 2a and S14-S16 †), single DABCO and carbonyl resonances at 47.6 and 171.2 ppm are consistent with those previously observed for the np orthorhombic structure of 1IAB.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In the 13 C cross-polarisation (CP) magic-angle spinning (MAS) NMR spectrum of 1IMOAB (Fig. 2a and S14-S16 †), single DABCO and carbonyl resonances at 47.6 and 171.2 ppm are consistent with those previously observed for the np orthorhombic structure of 1IAB.…”
Section: Resultssupporting
confidence: 84%
“…MOAB was occluded within the pores of 1 by a previously described melt-inltration procedure. 13,37 The maximum loading level obtained was 1.25 MOAB molecules per pore (Fig. S1, S2 and Tables S1-S3 †).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The azobenzene moiety has been investigated in the context of metal-organic framework (MOF) materials either as an intrinsic linker or a kind of surface additive. [34][35][36] Most related to the present study, we recently demonstrated a photo-switched water molecule capture/release behavior for ALD/MLD-grown MOF-like Feazobenzene thin films. 34 In the present work we now embed separate azobenzene layers in the ferrimagnetic ε-Fe 2 O 3 matrix for well-defined superlattice (SL) structures to challenge the photocontrol of the unique magnetic properties of the ε-Fe 2 O 3 phase.…”
Section: Introductionsupporting
confidence: 58%
“…Fotovoltaica: Recientes investigaciones [29] presentan la aplicación de un material cristalino, basado en un tipo de marco orgánico-metálico -MOF, una red de iones metálicos unidos por moléculas basadas en el carbono para formar estructuras tridimensionales, estos pueden formar materiales compuestos, al contener otras pequeñas moléculas, dentro de sus estructuras, que le permiten capturar energía, los investigadores expusieron el material a la luz UV, encontrando que la energía potencial puede almacenarse durante largos períodos de tiempo a temperatura ambiente y se puede liberar a demanda.…”
Section: Lazo Interno De Realimentación (A Nivel De Convertidor)unclassified